PENGARUH MOTIVASI DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN MELALUI KEPEMIMPINAN PADA PT SWADHARMA SARANA INFORMATIKA - Rahardi, Dedi Rianto; Permatasari, Aena Luthfiyani; Nandaika, Alfina; Anisa Noviyanti (Jurnal Nusa Manajemen, 2024)
This study investigates the effects of leadership and organizational culture on employee motivation within PT. Swadharma Sarana Informatics, with organizational performance considered an intermediary factor. Employing quantitative research methods, the study aims to quantify the interrelations among these variables. Data collection involved distributing questionnaires to 100 randomly selected civil servants at PT. Swadharma Sarana Informatics. SmartPls 3.0 software was used for data analysis. Initial findings suggest that organizational culture negatively impacts organizational performance but positively influences employee motivation at PT. Swadharma Sarana Informatics. Leadership shows a positive and significant effect on organizational performance within the organization. However, it does not significantly influence employee motivation.Additionally, organizational performance does not significantly impact employee motivation. Furthermore, organizational performance does not act as an intermediary factor between leadership and motivation, nor between organizational culture and motivation within PT. Swadharma Sarana Informatics